Isolation of zizyberenalic acid and biological studies of Ziziphus mauritiana Lam. growing in Bangladesh (Bangladesh Journal of Botany, 2019)
Ziziphus mauritiana Lam. was assessed for phytochemical constituent, antioxidant and cytotoxic activities. Powder prepared from the air-dried leaf was extracted with methanol. The concentrated extract was partitioned with petroleum ether, carbon-tetrachloride, and chloroform. A triterpenoid acid was isolated from the petroleum ether soluble fraction of the plant extract by gel permeation chromatography using Sephadex LH-20 followed by preparative thin layer chromatography over silica gel. The structure of the isolated compound was elucidated as zizyberenalic acid (1) by extensive analysis of its NMR spectral data and confirmed by comparison with published value. The methanol extract (IC50 = 7.37 ± 0.38 μg/ml) and its chloroform soluble materials (IC50 = 24.14 ± 0.53 μg/ml) produced strong antioxidant effect where it was comparable to standard agent tert-butyl-1-hydroxy toluene (IC50 = 32.47 ± 0.72 μg/ml) in DPPH free radical assay. The petroleum ether soluble fraction also showed strong cytotoxicity (LC50 = 1.31 ± 0.01 μg/ml) in brine shrimp lethality assay which was comparable to the standard drug, vincristine sulfate (LC50 = 0.31 ± 0.01 μg/ml). The results of the present study suggest that the plant leaf could be considered as a significant natural source for the development of antioxidant as well as cytotoxic compounds.